Effect of Kv3 channel modulators on auditory temporal resolution in aged Fischer 344 rats - Rybalko, Natalia; Popelář, Jiří; Šuta, Daniel; Svobodová Burianová, Jana; Alvaro, Giuseppe S; Large, Charles H; Syka, Josef (Hearing research, 2021)
AUT00063 and AUT00202 are novel pharmaceutical modulators of the Kv3 subfamily of voltage-gated K+ channels. Kv3.1 channels, which control fast firing of many central auditory neurons, have been shown to decline with age and this may contribute to age-related deficits in central auditory processing. In the present study, the effects of the two novel compounds that specifically modulate Kv3 channels on auditory temporal processing were examined in aged (19-25-month-old) and young-adult (3-5 month-old) Fischer 344 rats (F344) using a behavioral gap-prepulse inhibition (gap-PPI) paradigm. The acoustic startle response (ASR) and its inhibition induced by a gap in noise were measured before and after drug administration. Hearing thresholds in tested rats were evaluated by the auditory brainstem response (ABR). Aged F344 rats had significantly higher ABR thresholds, lower amplitudes of ASR, and weaker gap-PPI compared with young-adult rats. No influence of AUT00063 and AUT00202 administration was observed on ABR hearing thresholds in rats of both age groups. AUT00063 and AUT00202 had suppressive effect on ASR of F344 rats that was more pronounced with AUT00063. The degree of suppression depended on the dose and age of the rats. Both compounds significantly improved the gap-PPI performance in gap detection tests in aged rats. These results indicate that AUT00063 and AUT00202 may influence intrinsic firing properties of neurons in the central auditory system of aged animals and have the potential to treat aged-related hearing disorders.
Keywords: sluchové kmenové evokované potenciály; potkani inbrední F344; Shaw Potassium Channels; zvířata; akustická stimulace; krysa rodu Rattus; draslíkové kanály Shaw; úleková reakce; Animals; Evoked Potentials, Auditory, Brain Stem; Auditory Perception; sluchový práh; Reflex, Startle; Prepulse Inhibition; prepulsní inhibice; sluchová percepce; Acoustic Stimulation; Rats; Auditory Threshold; Rats, Inbred F344